Removal of Phenol from Water by Commercial Coconut Shell Charcoal - Anh, Tran Nam; Duong, Dao Van; Huan, Nguyen Xuan; Hanh, Nguyen Thi; Hien, Nguyen Thi; Linh, Dang Thi Hai; Hoang, Nguyen Minh; Trang, Hoang Thu (VNU Journal of Science: Natural Sciences and Technology, 2023)
In this study, phenol was adsorbed by commercial coconut shell charcoal (CSC), which is inexpensive, commercially available, non-toxic, and environmentally friendly. The measurements, namely the density functional theory (DFT) calculation, the energy-dispersive X-ray spectroscopy (EDS), and the Fourier-transform infrared spectroscopy (FTIR), were conducted to characterize the features of the CSC. The highest phenol removal efficiency reached 78.62% at optimal conditions (pH: 7, initial concentration of phenol: 20 mg/L, adsorption time: 120 minutes, and dosage of CSC: 2.5 g/L). The phenol adsorption process follows the Langmuir adsorption model with the coefficient R 2 = 0.9964. The maximum adsorption capacity by the CSC was determined to be 14.32 mg/g. The process of desorption of phenol from CSC was most effective in the NaOH solution. On the other hand, the adsorption efficiency of CSC gradually decreased after five consecutive cycles. At the fifth use, the phenol uptake efficiency reached 22.2%.